The Effectiveness of Group Counseling Using Cognitive Restructuring Techniques in Addressing Low Self-Confidence Among Bullying Victims - Endah Rahmawati; Lyana Nurmaningsih (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Bullying is a form of aggressive behavior that harms others and can have detrimental consequences for its victims. One of the adverse effects of bullying is low self-confidence among students who experience it. This study aimed to examine the effectiveness of group counseling using cognitive restructuring techniques in improving the self-confidence of students who are victims of bullying. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group. The population consisted of 44 students from two different classes. From this population, 24 students identified as having low self-confidence were selected as the research sample. Pretests and posttests were administered to determine differences between the experimental and control groups. Data were collected using a Likert-scale self-confidence instrument, in which higher scores indicated lower levels of self-confidence. Data were analyzed using an Independent Samples t-test in JASP software. The results revealed a difference in posttest scores between the experimental and control groups. The experimental group obtained a posttest mean score of 32.75, whereas the control group obtained a mean score of 42.08. The lower posttest score in the experimental group indicates that students who received group counseling with cognitive restructuring techniques demonstrated greater improvements in self-confidence than those in the control group. These findings suggest that group counseling with cognitive restructuring techniques is effective in addressing low self-confidence among students who are victims of bullying.